Life and Matter: A Criticism of Professor Haeckel's "Riddle of the Universe" - Lodge, Oliver, Sir, 1851-1940 (Salt Lake City, UT : Project Gutenberg, 2008)
"Life and Matter: A Criticism of Professor Haeckel's 'Riddle of the Universe'" by Sir Oliver Lodge is a scientific critique written in the early 20th century. This work focuses on the philosophical discourse surrounding materialism and the concept of monism as presented by Professor Ernst Haeckel, specifically aiming to critique and reevaluate Haeckel s conclusions about the relationship between life and matter. Lodge seeks to clarify misconceptions about the nature of life, consciousness, and their connection to material existence, emphasizing a more nuanced understanding of these complex subjects. The opening of "Life and Matter" sets the stage for an in-depth discussion on the philosophical implications of Haeckel's ideas. Lodge begins by establishing the context of scientific inquiry versus philosophy, cautioning against the extreme conclusions drawn by materialists like Haeckel, who equate the essence of life solely with material processes. He critiques Haeckel's perspectives on the unity of mind and matter, challenging the assumption that consciousness is merely a byproduct of physical interactions. Instead, Lodge advocates for a more comprehensive approach that considers the interplay of various forces, both material and immaterial, and raises questions about the true nature of existence, promoting a rational exploration of life's complexities beyond mere physicality. (This is an automatically generated summary.)
Release date is 2008-08-15
Keywords: Philosophy and religion; Monism; Life -- Origin; Haeckel, Ernst, 1834-1919. Welträthsel